The immunogenicity and safety of an inactivated quadrivalent influenza vaccine and a 23-valent pneumococcal polysaccharide vaccine in individuals with chronic diseases - Tang, Wanqin; Lu, Xi; Zhu, Zhongkui; Yu, Dan; Liu, Huaxian; Song, Yufei; Shen, Lu; Yu, Yang; Zhao, Yanwei; Xie, Yan (Frontiers in Immunology, 2025)
BackgroundThe inactivated quadrivalent influenza vaccine (IIV4) and the 23-valent pneumococcal polysaccharide vaccine (PPSV23) are widely administered. However, there was limited clinical evidence on the immunogenicity and safety of administration of the two vaccines in individuals with chronic diseases, especially concerning simultaneous administration.MethodsA total of 480 participants aged ≥60 years were randomly assigned to receive simultaneous or separate administration of IIV4 and PPSV23 and categorized into the Chronic Disease group or Healthy group based on their baseline health status. Blood samples were drawn before and 28 days after each vaccination to test the antibodies against all four influenza virus strains and 23 pneumococcus serotypes.ResultsThe geometric mean titer ratios (Chronic Disease group/Healthy group) of influenza antibodies ranged from 1.04 to 1.37 in the whole population and from 1.02 to 1.39 in the simultaneous administration population. The geometric mean concentration ratios of pneumococcal antibodies ranged from 0.87 to 1.12 in the whole population and from 0.97 to 1.33 in the simultaneous administration population. All ratios met the criteria for non-inferiority. The rate of adverse events was 0.96% in the Chronic Disease group and 1.47% in the Healthy group, with most events being mild (grade 1). No serious adverse events were observed.ConclusionThe immunogenicity and safety profiles of IIV4 and PPSV23, particularly when administered simultaneously, in individuals with chronic diseases were comparable to those in healthy individuals, supporting the vaccination strategy of IIV4 and PPSV23 in chronic disease population.